2018
DOI: 10.3390/polym11010033
|View full text |Cite
|
Sign up to set email alerts
|

PCL/POSS Nanocomposites: Effect of POSS Derivative and Preparation Method on Morphology and Properties

Abstract: The incorporation of polyhedral oligomeric silsesquioxanes (POSS) molecules as nanoparticles into polymers can provide improved physico-chemical properties. The enhancement depends on the extent of dispersion of the nanofiller, which is determined by the compatibility with the polymer that is by the POSS type, and the processing method. In this study, poly(ε-caprolactone)/POSS derivatives nanocomposites (PCL/POSS) were obtained via solution-casting and melt compounding. Two amino-derivatives containing differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 45 publications
0
21
0
Order By: Relevance
“…The DSC curves of the PCL/APIBPOSS nanocomposites, in addition to the exothermic peak corresponding to the PCL crystallization, exhibit another small exothermic transition in the temperature range 41–47 °C (inset of Figure 1b–d) that corresponds to the APIBPOSS crystal formation. As we previously reported [22], APIBPOSS crystallizes and agglomerates in PCL matrix due to the POSS–POSS interactions. Due to the amorphous nature of APIOPOSS, the DSC curves of PCL/APIOPOSS composites exhibit only the exothermic crystallization peak of PCL.…”
Section: Resultsmentioning
confidence: 58%
See 3 more Smart Citations
“…The DSC curves of the PCL/APIBPOSS nanocomposites, in addition to the exothermic peak corresponding to the PCL crystallization, exhibit another small exothermic transition in the temperature range 41–47 °C (inset of Figure 1b–d) that corresponds to the APIBPOSS crystal formation. As we previously reported [22], APIBPOSS crystallizes and agglomerates in PCL matrix due to the POSS–POSS interactions. Due to the amorphous nature of APIOPOSS, the DSC curves of PCL/APIOPOSS composites exhibit only the exothermic crystallization peak of PCL.…”
Section: Resultsmentioning
confidence: 58%
“…The decrease in crystallinity is not the expected behavior for APIBPOSS-based nanocomposites since the above results suggest that it acts as nucleating agent. The liquid APIOPOSS exhibits higher compatibility with PCL than the crystalline solid APIBPOSS, which was attributed to the more thermodynamically favorable interactions between PCL and APIOPOSS [22]. The better compatibility leads to better dispersion; hence, smaller size aggregates were found in the case of PCL/APIOPOSS blends.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, by comparing the effects of APIB-POSS and AEAPIB-POSS on polyurethane foam, Członka et al [ 21 ] showed that the content of the filling material has a great influence on the foam. Cobos et al [ 22 ] studied the effects of different types and contents of POSS on various properties of PCL-derived composites. Niemczyk et al [ 23 ] studied a new type of POSS and applied it to the flame retardant aspect of PP materials.…”
Section: Introductionmentioning
confidence: 99%